An Appeal for a Creaturely Attitude to Animals in Vasily Rozanov’s Writing - Mondry, Henrietta (Poznańskie Studia Slawistyczne, 2022)
The work of Vasily Rozanov offers a relevant case study of our changing relation to natural-cultural contact zones with animals. Rozanov used a comparative approach to human-animal connections to change the societal attitude to the physical body and erase boundaries between human and animal corporeality. I focus on his narratives that promote a creaturely attitude to animals in the context of societal problems. The issues he addresses have special relevance to the current pandemic realia. I argue that Rozanov used both ethico-religious and secular arguments, as well as logic and emotion as part of his strategy to appeal to wider audiences. The hybrid genre of his narratives was a new form of literature that employed multiple rhetorical devices in creating creaturely poetics.